Parental alarm calls suppress nestling vocalization - Dirk Platzen; Robert D. Magrath (2004)
Evolutionary models suggest that the cost of a signal can ensure its honesty. Empirical studies of nestling begging imply that predator attraction can impose such a cost. However, parents might reduce or abolish this cost by warning young of the presence of danger. We tested, in a controlled field playback experiment, whether alarm calls cause 5-, 8- and 11-day-old nestlings of the white-browed scrubwren, Sericornis frontalis, to suppress vocalization. In this species, nestlings vocalize when parents visit the nest ('begging') and when they are absent ('non-begging'), so we measured effects on both types of vocalization. Playback of parental alarm calls suppressed non-begging vocalization almost completely but only slightly reduced begging calls during a playback of parental feeding calls that followed. The reaction of nestlings was largely independent of age. Our results suggest two reasons why experiments ignoring the role of parents probably overestimate the real cost of nestling vocalizations. Parents can warn young from a distance about the presence of danger and so suppress non-begging vocalizations that might otherwise be overheard, and a parent's presence at the nest presumably indicates when it is safe to beg.